2005
DOI: 10.1371/journal.pgen.0010068.eor
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the HSD17B1 gene and risk of prostate cancer

Abstract: Steroid hormones are believed to play an important role in prostate carcinogenesis, but epidemiological evidence linking prostate cancer and steroid hormone genes has been inconclusive, in part due to small sample sizes or incomplete characterization of genetic variation at the locus of interest. Here we report on the results of a comprehensive study of the association between HSD17B1 and prostate cancer by the Breast and Prostate Cancer Cohort Consortium, a large collaborative study. HSD17B1 encodes 17b-hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…concentrations (Chen et al, 2003) but an Australian cohort study showed no association with baseline plasma E2 levels (Severi et al, 2006). A large international pooled analysis yielded no evidence for an association with polymorphisms of the HSD17B1 gene, which encodes the 17HSD type 1 enzyme that converts estrone to the more active E2 (Kraft et al, 2005).…”
Section: Estrogensmentioning
confidence: 99%
“…concentrations (Chen et al, 2003) but an Australian cohort study showed no association with baseline plasma E2 levels (Severi et al, 2006). A large international pooled analysis yielded no evidence for an association with polymorphisms of the HSD17B1 gene, which encodes the 17HSD type 1 enzyme that converts estrone to the more active E2 (Kraft et al, 2005).…”
Section: Estrogensmentioning
confidence: 99%
“…P 450 aromatase (CYP17A1), which is expressed in granulosa cells, converts androstenedione (A) and testosterone (T) to estrone (E1) and 17β‐estrone (E2), respectively. Meanwhile, HSD17B1 encodes a member of the 17β‐HSD family that converts estrone into estradiol in ovarian tissue (Kraft et al, ). Granulosa cells respond to FSH signaling by increasing the expression of CYP17A1 and 17β‐HSD.…”
Section: Discussionmentioning
confidence: 99%
“…htSNPs were selected based on the efforts of the Breast and Prostate Cohort Consortium (BPC3) (15), as previously described (12, 16). Given the close proximity of the adjacent genes, including N-acetylglucosaminidase-α ( NAGLU ) gene and a pseudogene for HSD17B1 ( HSD17BP1 ) in the 5′ direction and CoA synthase ( COASY ) and transcription factor-like 4 ( TCFL4 ) in the 3′ direction, the location of htSNPs for HSD17B1 extended into these neighboring genes.…”
Section: Methodsmentioning
confidence: 99%